Transformation of commemorative practices in Ukrainian historical discourse - Roman Dodonov (Cхід, 2022)
The article is devoted to the study of changes taking place in Ukrainian society in the field of content of historical memory and forms of commemorative practices. The purpose of the study is to identify the main trends in transformations of the form and content of commemorative practices in the Ukrainian historical discourse. During the semi-structured, focused interview with 51 experts representing the main regions of Ukraine, it has been found that current commemorative practices are based on a symbiosis of monologue and dialogue models of memory. The remnants of the Soviet-style totalitarian worldview have led to the popularity of the model of memory, in which the state’s monopoly on history prevails. The idea that national memory consists of many particular commemorations is difficult for Ukrainian society to accept. The past is a kind of symbolic resource, the use of which contributes to the legitimization of Ukraine as an independent state. However, the forms of commemoration remain largely old. Along with fundamentally new forms, primarily related to Internet technologies and social networks, in Ukraine, just as in the Soviet period, commemoration is focused on honoring heroes and victims. At the same time, there is a radical reassessment: the heroes of the Soviet era have become villains, and villains have become heroes. All this points to the “hybrid nature” of commemorative practices with an emphasis on the martyrological-victim component and the trauma of the social psyche of Ukrainians.